Evaluación Periodontal en las estudiantes de sexo femenino de la Modalidad de Estudios Presencial de la Universidad Nacional de Loja en el periodo mayo - julio del 2014. - Caraguay Ordóñez, Gabriela Paola (2014)
To evaluate periodontal status by applying the index of need for periodontal treatment (INTPC) and the index of periodontal disease of Ramfjord (IEP) in female students. Identify the local factors that contribute to the accumulation of bacterial plaque: aparatolog fixed orthodontics, dental crowding, and tooth decay also verify if the risk factor for periodontal disease is present: smoking. It is a descriptive study, sectional in applying the criteria for inclusion and/or exclusion as shown is 452 students between 18 and 30 years of age; used as an instrument of data collection the history dental clinic and the form of periodontics. When applying the index of need for periodontal treatment we have that the 50% that represents 225 students presented code 0; the 33% that represents 147 students presented code 1; the 17% that represents 78 students presented code 2; and 0.44 % that represents 2 students presented code 3. After applying the index of periodontal disease as Ramfjord, the results were as follows: in the 49% that corresponds to 221 students presented a code 0; the 30% that corresponds to 137 students presented code 1; the 21% that corresponds to 93 students presented code 2; and the 0.22 % that corresponds to 1 student presents code 3. In relation to the insertion loss 86% have no insertion loss in relation to 388 students; 13% which corresponds to 61 students have an insertion loss less than 3mm; the 0.66 % that represents 3 students have insertion loss of 3 to 6mm. The female students presented a periodontal tissue healthy according to the index (CPITN) in 50% and thus same presented periodontal tissue healthy according to the index (IEP) Ramfjord 49 %; and the factors that contribute to the accumulation of bacterial plaque: tooth decay is presented in a 79 %, dental crowding in the 45 %, fixed appliances of orthodontics in a 6.41 %. KEY WORDS: periodontal evaluation, bacterial plaque, CPITN, IEP, local factors, risk factors.